A novel antibacterial titania coating: Metal ion toxicity and in vitro surface colonization - Detsch, Rainer; et al. (Journal of Materials Science: Materials in Medicine, 2005)
Postoperative implant-associated infection is still an unresolved and serious complication in modern surgery. Antibacterial and biocompatible surfaces could both reduce infection rates and promote tissue integration. In this respect, a comparative study of the antibacterial as well as the biocompatible potential of different metal ions in vitro is presented. The assays used were growth inhibition tests with different metal salts carried out with tissue cells and bacteria under corresponding culture conditions. Additionally, in vitro tests in direct surface contact with tissue cells and bacteria onto a novel copper containing sol-gel derived titanium dioxide coating (Cu-TiO) and a fourfold Cu-TiO coating were performed. The values were compared to a non-filled titanium dioxide coating and standard Ti6Al4V alloy. SEM-investigations were performed to approve the results of the in vitro tests. Among Ag, Zn, Co, Al and Hg, the growth inhibition tests revealed an outstanding position of copper ions as antibacterial but nevertheless bio-tolerant additive. These results were affirmed by the cell tests in direct surface contact and SEM-investigations, where best cell growth was found on the Cu-TiO coatings. Highest antibacterial properties with a tolerable cytocompatibility could be observed on the fourfold Cu-TiO coatings. Consequently, surfaces with custom-tailored antibacterial properties may be established and could be of particular interest in revision and tumor arthroplasty. © 2005 Springer Science + Business Media, Inc.